Teaching Grammar in Context: Is it Effective For Increasing Student’s Achievement in Grammar Rules? - Sintadewi, Ni Made Dita; Kurniawati, Kadek Lina (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine the role of grammar teaching in improving students' mastery of grammar rules and learning achievement through a Systematic Literature Review (SLR) approach. This study reviewed reputable journal articles published between 2013 and 2024 and selected based on predetermined inclusion and exclusion criteria. The data collection process followed the SLR stages, which included identification, screening, and assessment of article eligibility. The collected data were then analyzed using thematic synthesis to group and interpret the main findings from previous studies. The review results showed that teaching grammar in context consistently had a positive impact on improving students' mastery of grammar rules. In addition, this approach helps students use grammar more meaningfully in both oral and written communication. The application of grammar in context is generally carried out through the use of dialogue, stories, authentic texts, and audiovisual media. Based on these findings, it can be concluded that teaching grammar in context is an effective approach to improving grammar mastery and supporting the development of students' written and oral language skills.